Users’ Perception on Interior Design of Tarumanegara Knowledge Center Library - Lili Sudria Wenny; Fanny Nuravianti (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2021)
This study aimed to know the users’ perception of spatial planning in the Tarumanagara Knowledge Center (TKC), Library of Tarumanegara University. It was a descriptive quantitative study that relied on the users’ perception on the spatial planning of the knowledge center as the primary sources. While, the sample involved in the study comprised 90 people who visited the knowledge center taken randomly. Data collection techniques used a Likert scale-based questionnaire distributed to the targeted visitors or users. The collected data were then analyzed using a descriptive statistic. The results showed that the user's perception of the principles in the library layout obtained an average score of 3.07 that meant Good. Perceptions of aspects in library spatial planning get an average score of 3.20 that meant Good. Library users' perceptions of patterns in library layout get an average score of 3.14 that meant Good. Library users' perceptions of the spatial library get an average score of 3.18 that meant Good. Library users' perceptions of library space arrangement get an average score of 2.82 that meant Good. While the final score of the overall average of 3.06 that felt into Good category. It can be concluded that Tarumanegara knowledge Center with its spatial planning was able to provide comfortable rooms and facilities that satisfied the users to access available sources.